Estimating the impacts of urban growth on future flood risk : A Comparative Study - Veerbeek, Willem, author; Zevenbergen, C., supervisor; Unesco-IHE Institute for Water Education; Institute for Water Resources; Delft University of Technology (Leiden, Netherlands : CRC Press, 2017)
The unprecedented growth of cities has a significant impact on future flood risk that might exceed the impacts of climate change in many metropolitan areas across the world. Although the effects of urbanisation on flood risk are well understood, assessments that include spatially explicit future growth projections are limited. This comparative study provides insight in the long term development of future riverine and pluvial flood risk for 18 fast growing megacities. The outcomes provide not only a baseline absent in current practise, but also a strategic outlook that might better establish the role of urban planning in limiting future flood risk.